Advances in oncolytic herpes simplex virus and adenovirus therapy for recurrent glioma - Hu, Mingming; Liao, XuLiang; Tao, Yi; Chen, Yaohui (Frontiers in Immunology, 2023)
Recurrent glioma treatment is challenging due to molecular heterogeneity and treatment resistance commonly observed in these tumors. Researchers are actively pursuing new therapeutic strategies.Oncolytic viruses have emerged as a promising option. Oncolytic viruses selectively replicate within tumor cells, destroying them and stimulating the immune system for an enhanced anticancer response. Among Oncolytic viruses investigated for recurrent gliomas, oncolytic herpes simplex virus and oncolytic adenovirus show notable potential. Genetic modifications play a crucial role in optimizing their therapeutic efficacy. Different generations of replicative conditioned oncolytic human adenovirus and oncolytic HSV have been developed, incorporating specific modifications to enhance tumor selectivity, replication efficiency, and immune activation. This review article summarizes these genetic modifications, offering insights into the underlying mechanisms of Oncolytic viruses' therapy. It also aims to identify strategies for further enhancing the therapeutic benefits of Oncolytic viruses. However, it is important to acknowledge that additional research and clinical trials are necessary to establish the safety, efficacy, and optimal utilization of Oncolytic viruses in treating recurrent glioblastoma.